2018
DOI: 10.3390/molecules23082032
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Attenuates Acetaminophen-Induced Liver Injuries in Mice by Activating the Nrf2 Signaling Pathway

Abstract: Acetaminophen (APAP) is a well-known antipyretic and analgesic drug. However, the accidental or intentional APAP overdose will induce liver injury and even acute liver failure. Astragaloside IV (AS-IV), a bioactive compound isolated from Astragali Radix, has been reported to have protective effects on the digestive and immune systems because of its anti-oxidant and anti-inflammatory properties. This study aims to observe whether AS-IV pretreatment provides protection against APAP-induced liver failure. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…In traditional Chinese formula, AR is often used for the treatment of liver fibrosis [ 10 ]. Although the protective effects of AR on liver injury and related mechanisms have been reported [ 9 , 11 ], the studies on the effect and mechanism of AR on liver fibrosis are still lacking. More importantly, toxicological study has confirmed the high safety of AR.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese formula, AR is often used for the treatment of liver fibrosis [ 10 ]. Although the protective effects of AR on liver injury and related mechanisms have been reported [ 9 , 11 ], the studies on the effect and mechanism of AR on liver fibrosis are still lacking. More importantly, toxicological study has confirmed the high safety of AR.…”
Section: Introductionmentioning
confidence: 99%
“…However, NAC has its limits, such as the short administration period post APAP toxicity (6-8 h). In recent years, a lot of effort has been made to investigate the preventive and therapeutic method for APAP toxicity, especially Chinese herbal medicines (4)(5)(6) and some accepted old drugs.…”
mentioning
confidence: 99%
“…The most common used drugs for inducing ALF mainly include D-galactosamine (D-gal) [7,22], acetaminophen (APAP) [26][27][28][29], thioacetamide (TAA) [30], and carbon tetrachloride (CCl 4 ) [31]. In most drug models of ALF, there are nephrotoxicity, cardiotoxicity and other organ damage besides hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%